2020
DOI: 10.1177/1179573520976832
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Transcranial Direct Current Stimulation in Changing Resting-State Functional Connectivity in Patients With Neurological Disorders: A Systematic Review

Abstract: Background: People with neurological disorders are found to have abnormal resting-state functional connectivity (rsFC), which is associated with the persistent functional impairment found in these patients. Recently, transcranial direct current stimulation (tDCS) has been shown to improve rsFC, although the results are inconsistent. Objective: We hope to explore whether tDCS induces rsFC changes among patients with neurological disorders, whether rsFC is clinically relevant and how different tDCS parameters af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…The acute properties are due to the primary polarization mechanism that induces changes in ionic concentrations (Na+, Ca+, K+, Cl-), alteration of the pH balance, and transmembrane protein variations by synaptic 40 and non-synaptic mechanisms 41 . Active tDCS can induce changes in both local (ie, brain regions under the transcranial electrodes) and diffuse (ie, brain regions remote to the electrodes) regions considering the brain as an anatomic and functional complex neuronal network 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The acute properties are due to the primary polarization mechanism that induces changes in ionic concentrations (Na+, Ca+, K+, Cl-), alteration of the pH balance, and transmembrane protein variations by synaptic 40 and non-synaptic mechanisms 41 . Active tDCS can induce changes in both local (ie, brain regions under the transcranial electrodes) and diffuse (ie, brain regions remote to the electrodes) regions considering the brain as an anatomic and functional complex neuronal network 42 .…”
Section: Discussionmentioning
confidence: 99%
“…But in Polania's study, they used electrodes on a 5 × 7 cm area, which covered many brain regions, to deliver current to the scalp. A previous study showed that the size of the electrodes is a factor in modulating the stimulation effect [ 20 ]. In the study of Ho [ 21 ], they found that stimulated with a larger size induced a cumulative enhance in cortical excitability, but not a smaller electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous studies, we found that theta power ( Thibaut et al, 2018 ) and alpha power ( Chennu et al, 2014 ; Cai et al, 2019 ) were significantly and positively correlated with behavioral scores based on the CRS-R. Several studies have confirmed that increased theta, alpha and beta power indicates a better state of consciousness ( Sitt et al, 2014 ; Chennu et al, 2017 ; Huang et al, 2020 ). The effect of tDCS can also appear in other brain regions besides the stimulation site ( Krause et al, 2017 ; Chan and Han, 2020 ). In our study, the stimulation site was in the DLPFC, but the final EEG PSD was significantly different in the parieto-occipital region.…”
Section: Discussionmentioning
confidence: 99%